Estimating External Costs of Transportation in Regional Areas: Using Available Statistical Data the Case of the Region of Campania - Gallo, Mariano (TeMA - Journal of Land Use, Mobility and Environment, 2010)
In this paper simplified methods for estimating the external costs due to transportation in regional areas are proposed. The methods are based on data available by national and regional statistical sources and do not need specific surveys; they allow obtaining approximate estimates useful for a preliminary evaluation of transportation plans, policies and projects. In more detail, a negative externality is defined as a cost that is produced by subject A and is borne by subject B; moreover, subject A does not consider the effects of his/her behavior on subject B and does not compensate subject B for the costs that this last one is forced to bear. In this paper after a literature review on methodologies proposed for estimating external costs, in national and international ambits, the main external costs produced by transportation systems in the Region of Campania are estimated. The main external costs considered are: greenhouse gas emissions, air pollution, noise, accidents and congestion. In the paper the secondary external costs are neglected; the main ones are: water and soil pollution; landscape and nature damages; upstream and downstream effects; visual intrusion; separation effects; soil occupancy. In this paper the external costs estimated are the ones produced not only by road traffic, that anyway is the main “culprit”, but also by rail and air transportation systems. The evaluation of external costs has required the collection of several data on the regional mobility and the estimation of veh-kms per year produced in Campania by cars and freight vehicles. The estimation of veh-kms per year is based on circulating vehicles, subdivided by the COPERT classification, and on average yearly distances covered by each vehicle class. Other regional statistical data are collected about regional rail transport and air services at the main airports of the region. Moreover, since the evaluation of some external costs is based on damages on human health, it required to give a value to human life and to health damages. The results show as the largest costs are due to air pollution (38.0 %) and accidents (28.2 %); noise amounts to 18.4 %, while less importance is assumed by congestion (10.6 %) and greenhouse gas emissions (4.8 %). Moreover, the results show also as the amount of external costs overcomes 4 € billions per year and is equal about to 4.7 % of regional GDP; in particular, it is highlighted as the environmental costs (greenhouse gas emissions, air pollution and noise) overcome 60 % of total costs. The obtained results have shown as the external costs are significant respect to other costs of transportation systems and as they should be always evaluated when public funds are invested for improving transportation systems.